Thermographical Analysis of Continuing Tradition of Mirror Casting in Kerala - Takekazu NAGAE; Sharada SRINIVASAN; Srinivasa RANGANATHAN; R. M. PILLAI; Yasuji SHIMIZU and Haruhisa MIFUNE (ISIJ International, 2014)
Additions of large amounts of tin to copper lead to high tin bronzes with interesting combination of properties. Such high tin bronzes need to be carefully processed to avoid brittleness in compositions cor- responding to beta and delta phases. The latter has been used in China, India, Korea and Japan to pro- duce distortion free mirror images. This investigation is concerned with the bronze mirror from India where the tradition has survived in the village Aranmula in Kerala. The alloy has an exceptionally high tin content consisting almost entirely of the delta phase, which is an intermetallic compound (Cu 31 Sn 8 ) of composition 32.6% tin. This is an ideal alloy to be polished into a mirror due to the silvery white color and high hardness. Its high brittleness is offset by an ingenious casting and polishing process. In addition to studying the composition and the casting involving a mould cum crucible method, ther- mographic analysis has been employed to follow the solidification sequence by looking at the thermal pro- file. It is correlated with the actual composition, processing parameters and the resultant microstructure, due to the cooling rate the alloy solidifies with a mild departure from the equilibrium phase diagram. Some observations regarding the structure of the delta phase which is a Hume-Rothery phase will be pro- vided about its optical and mechanical properties.